Music in the disruptive era - Hurwitz, David 1961-; Ordóñez Eslava, Pedro (Brepols, 2022)
"Music in the Disruptive Era" contains fifteen essays assessing the impact of today’s revolutionary digital technologies on the ways audiences and industry professionals perceive, compose, consume, research, and communicate about music. After an initial assessment of "the Disruptive Era" in a series of six snapshots offering a summary and review of some of the technological challenges (and opportunities) confronting both music producers and consumers, a group of international scholars considers the impact of the digital era in three major areas. First, there is the revolution in data storage and retrieval, with online archives and other digital resources making an unprecedented volume and diversity of information available to scholars and researchers for the first time - all from the convenience of a home desktop. Second, three essays assess some of the myriad ways in which composers and music industry professionals have been influenced by the potentialities and discontinuities of the current age to find creative inspiration, attract new audiences, and reimagine traditional musical idioms. Finally, on the cutting edge of the digital divide, scholarly contributors examine two of the countless new genres birthed by the advent of the latest technological innovations: specifically, the "meme" and the "video loop." (Verlag)
Keywords: Innovation; Datenspeicherung; Neue Technologie; Musik; Aufsatzsammlung